Progress in Corrosion Science and Engineering I - Pyun, Su-Il; Lee, Jong-Won (Modern Aspects of Electrochemistry, 2010)
Topics in Number 46 include: Comprehensive review of the structural aspects and anti-corrosion properties of passive films on metals and alloys; a detailed description is given of the nucleation and growth of 2-dimensional passive films at earlier stages, their effect on the corrosion properties of metal surfaces, and the nanostructures of 3-dimensional passive films Research on nano- and micro-fabrications based on anodizing treatments combined with chemical/mechanical processes such as laser irradiation, atomic force micro-probe processing, and thin film deposition techniques Passivity of aluminum-based amorphous alloys and stainless steels and the catalytic activity of copper-based amorphous alloys Theoretical analysis of the admittance behavior of passive film/electrolyte junction based on the theory of amorphous semiconductor Schottky barriers From reviews of previous volumes: "This long-standing series continues its tradition of offering high quality reviews of established and emerging subject areas, together with the less common aspects of electrochemical science... [and]... deserves a place in electrochemistry libraries and should prove useful to electrochemists and related workers." -Chemistry and Industry "Continues the valuable service that has been rendered by the Modern Aspects series." -Journal of Electroanalytical Chemistry "Will definitely be of much use to researchers in the field of electrochemistry. . . . The editors of this well-produced volume deserve all appreciation for maintaining the excellent standard of the series." -Bulletin of Electrochemistry "Extremely well-referenced and very readable.... Maintains the overall high standards of the series." -Journal of the American Chemical Society.